Looking Beyond September 11: Islam in the West ‒ and Democratic Trends in the Middle East and North Africa (American Journal of Islam and Society, 2012)
The Fortieth Annual AMSS (Association of Muslim Social Scientists ofNorth America) Conference, held at John Jay College at the City Universityof New York in New York City, marked a decade since September 11 by reviewingthe past ten years of the Muslim narrative, with particular focus onthe past year and the considerable social and political changes in the MiddleEast and North Africa. Welcomed by John Jay College Provost and SeniorVice President for Academic Affairs, Dr. Jane Bowers, and by outgoingAMSS President Dr. Ali Mazrui ‒ the conference’s one-day format ensuredan intensive and stimulating session, which captured the energy of the participantsand attendees that filled the symposium. While a four-panel conferencefeaturing only twelve presenters may appear small in comparison tosome academic meetings, AMSS again proved that quality eclipsed quantityin offering a diverse, yet deep analysis of contemporary issues ‒ ranging fromthe Arab Spring to domestic discourses highlighting and targeting Muslims.A panel entitled, “The Arab Spring: Paths to Democracy in the MiddleEast and North Africa,” opened the day’s proceedings by assessing the veryfluid and evolving situation in the heart of the Arab world. Khalid Madhi(Adjunct Professor at St. Xavier University and PhD Student Researchand Teaching Assistant at the University of Illinois at Chicago) focused onhow the transformative movements in Tunisia and Egypt would be felt inMorocco by offering a study of the country’s Islamist efforts. Umar Oseni(Visiting Fellow at the Islamic Legal Studies Program at the Harvard LawSchool and Post-doctoral Scholar and Lecturer at the International IslamicUniversity Malaysia) shifted the discussion from a specific country to amore regional approach when he proposed a model for conflict managementthat is inherent within Islam itself. Finally, Mohamed Nimer (AssistantProfessor of International Relations at the School of International ...